Experiences of college students with physical impairment during online classes in physical education - Cruz, Jan Carhley; Cruz, Jayvey; Abella, Jerizza; Castro, Wilrenz; Lobo, Joseph; Celis, Michael Louie; Bernardo, Bryan Dale (Edu Sportivo: Indonesian Journal of Physical Education, 2023)
Due to the rampant spread of COVID-19, schools have shut down worldwide, resulting in dramatic changes in education. Physically impaired students are one of the groups that were highly affected by these drastic changes. On a positive note, according to previously conducted studies, online physical education can provide students with disabilities a context in which self-efficacy and participation are promoted, which may lead to improved academic achievement. This qualitative-exploratory study is focused on unraveling the experiences and challenges of students with physical impairments during online PE classes amidst the pandemic. Ten (10) samples of college students within Pampanga, Philippines, participated in the study. This study has analyzed in-depth college students’ concepts, thoughts, and experiences during their online PE. Narratives from the participants were analyzed using manual qualitative analysis through transcriptions, coding, categorization, and thematic analyses. Based on the findings, three central themes have emerged: (a) becoming better, fitter, healthier, and happier; (b) overcoming challenges; and (c) having a healthy mind in a healthy body. Indeed, there is a need to ameliorate the delivery of acclimated or special needs physical education by making teachers more involved and dynamic in their tasks and lessons. PE teachers supervising students with physical impairments should determine their capacities and measures that need enforcement to support participation in sports and fitness. Aside from the findings discovered, an in-depth analysis of how academic performance, personality types, parental support, or sports participation can affect students’ perception or experience in online physical education classes is highly suggested.